Providing a Motivational Environment with Proper Associate Recognition - Clayton Becton; Allen Wysocki; Karl Kepner (EDIS)
This is EDIS document HR 023, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published July 2002.